Strategi Pengembangan Sistem Integrasi Sapi-Kelapa Sawit (SISKA) Pola Pemeliharaan Semi-Intensif di Kecamatan Pangkalan Lesung Kabupaten Pelalawan - Silviana Karina; Yusmini Yusmini; Jumatri Yusri (Politeknik Pertanian Negeri Payakumbuh, 2020)
This study aims to:1)describe internal and external factors, 2) formulate alternative development strategies, and set priorities for alternative SISKA development strategies. This research was conducted in the Pangkalan Lesung Subdistrict, Pelalawan Regency. The method used in this study is a survey method, and research respondents were 29 farmers and eight experts.Data analysis used SWOT to formulate alternative strategies and AHP for strategic priorities.The results showed that internal and external factors in the development of SISKA include internal strength factors, namely institutional factors that support and SISKAs efforts were relatively profitable. Internal weakness factors are the availability of limited resources and the low technical application of technology. External opportunity factors are institutional factors is the opportunity to support the potential price of cattle and the self-sufficiency of beef through SISKA. External threats are health, safety, and limited animal feed resources. The results showed strategies increasing cattle population, planning for palm oil rejuvenation, collaborating with PKS as a reliable provider, BIS and tankos, HR training on how to process biogas, providing extension services for livestock health and incubation cage as a place for handling sick animals, re-modification of the chopper machine and planting or cultivating grass.